2018
DOI: 10.1016/j.scriptamat.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Design of 0–3 type nanocomposites using hydrothermal sintering

Abstract: We report here the successful design of 0-3 type nanocomposites where 30 nm ferromagnetic metallically conducting cores of manganite La 0.66 Sr 0.34 MnO 3 (LSMO) are discretely distributed in an insulating silica matrix. Starting from LSMO@SiO 2 core@shell nanoparticles, hydrothermal sintering process was used as a low temperature densification route (300 °C, 350 MPa, 90 min) in presence of 0.2M aqueous sodium hydroxide solution. This process based on a pressure solution creep in the contact zones between nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A lot of efforts have been made to reduce the sintering temperatures of ceramics; some of those are inspired from the natural densification of geological and biological mineralization activities, in which a liquid phase, usually an aqueous solution, is involved in order to increase the driving force of densification. Representative examples include hydrothermal sintering, modified low‐temperature hydrothermal sintering, reactive hydrothermal liquid‐phase densification, room temperature fabrication of Li 2 MoO 4 ceramic, and cold sintering process, among which cold sintering is a low‐temperature sintering technology that has been recently developed. It has been demonstrated that many ceramics can be readily densified under low‐temperature conditions (temperature = 25–300 °C) with the assistance of a transient liquid phase .…”
Section: Introductionmentioning
confidence: 99%
“…A lot of efforts have been made to reduce the sintering temperatures of ceramics; some of those are inspired from the natural densification of geological and biological mineralization activities, in which a liquid phase, usually an aqueous solution, is involved in order to increase the driving force of densification. Representative examples include hydrothermal sintering, modified low‐temperature hydrothermal sintering, reactive hydrothermal liquid‐phase densification, room temperature fabrication of Li 2 MoO 4 ceramic, and cold sintering process, among which cold sintering is a low‐temperature sintering technology that has been recently developed. It has been demonstrated that many ceramics can be readily densified under low‐temperature conditions (temperature = 25–300 °C) with the assistance of a transient liquid phase .…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic transport is consequently strongly dependent on external magnetic field, which makes such composites promising for spintronic devices. Hydrothermal sintering is suitable to fabricate 0-3 type composites with a relative density of approximately 80-85% where LSMO cores are uniformly and discretely embedded in the insulating matrix of three-dimensional-connectivity that originates from the silica shell densification [43]. Here silica also ensures the confinement of defects at the interfaces and prevents the core growth.…”
mentioning
confidence: 99%
“…In addition to the sintering techniques categorized as Field Assisted Sintering Technology (e.g. Flash Sintering, Spark Plasma Sintering (SPS)) that are well recognized for advantageous enhanced kinetics [6][7][8], the exploration of non-equilibrium sintering, through transient liquid phase or by using solvent assisted sintering (Cold Sintering Process, Hydro-Solvothermal Sintering) was also shown to be particularly efficient for very low temperature sintering of functional oxides such as ZnO, BaTiO 3 , α-Quartz and composites [9][10][11][12][13][14][15]. Cool-SPS has also demonstrated the solventfree sintering of thermodynamically fragile materials, including reactive sintering of hydrated precursors at temperatures below 400°C [16][17][18].…”
Section: Abstract: Spark Plasma Sintering Amorphous Oxides Precursorsmentioning
confidence: 99%